Analgesia for spinal anesthesia positioning in elderly patients with proximal femoral fractures: Dexmedetomidine-ketamine versus dexmedetomidine-fentanyl. Issue 20 (15th May 2020) - Lee, Ki Hwa; Lee, Soo Jee; Park, Jae Hong; Kim, Se Hun; Lee, Hyunseong; Oh, Dae Seok; Kim, Yong Han; Park, Yei Heum; Kim, Hyojoong; Lee, Sang Eun
Abstract : Abstract: Elderly patients with femoral fractures are anticipated to endure the most pain caused by positional changes required for spinal anesthesia. To improve pain relief, we compared the analgesic effects of intravenous dexmedetomidine-ketamine and dexmedetomidine-fentanyl combinations to facilitate patient positioning for spinal anesthesia in elderly patients with proximal femoral fractures. Forty-six patients were randomly assigned to two groups and received either 1 mg/kg of intravenous ketamine (group K) or 1 μg/kg of intravenous fentanyl (group F) concomitant with a loading dose of dexmedetomidine 1 μg/kg over 10 minutes, then dexmedetomidine infusion only was continued at 0.6 μg/kg/h for following 20 minutes, and titrated at a rate of 0.2 to 0.6 μg/kg/h until the end of surgery. After completion of the infusion of either ketamine or fentanyl, the patients were placed in the lateral position with the fracture site up. The pain score (0 = calm, 1 = facial grimacing, 2 = moaning, 3 = screaming, and 4 = unable to proceed because of restlessness or agitation) was used to describe the pain intensity in each step during the procedure (lateral positioning, hip flexion, and lumbar puncture), and quality score (0 = poor hip flexion, 1 = satisfactory hip flexion, 2 = good hip flexion, and 3 = optimal hip flexion) was used to describe the quality of posture. Group K showed a median pain score of 0 (0-1), 0 (0–0) and 0 (0–0) in lateral positioning, hip flexion and lumbar puncture, respectively, while group F showed a score of 3 (2.75–3), 3 (2–3) and 0 (0–1), respectively. The pain score in lateral positioning ( P  < .0001) and hip flexion ( P  < .0001) was significantly lower in group K than group F . Group K showed the significantly higher quality scores of spinal anesthesia positioning ( P = .0044) than group F . Hemodynamic adverse effects, such as bradycardia, hypotension, and desaturation, were not significantly different between the groups. The administration of dexmedetomidine-ketamine showed a greater advantage in reducing pain intensity and increasing the quality with patient positioning during spinal anesthesia in elderly patients with proximal femoral fractures, without any serious adverse effects.